Student learning outcomes through technology-based online learning in the Biology Education Study Program - Riya Irianti; Sri Amintarti; Nurul Hidayati Utami (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
Online learning is an alternative solution in the learning process in the Covid-19 pandemic era. Technology plays a vital role as a teaching medium in the online learning process. This study aims to describe the learning outcomes of 323 Biology Education study program students. This research is a descriptive study with data obtained using observation sheet instruments to collect data related to online learning and documentation of learning outcomes scores which were analyzed using descriptive statistics. The technology used in online learning is Zoom Meeting, Google Metting, WhatsApp, Youtube, and LMS (Learning Management system) in the form of SIMARI. The results of this study indicate that the average student learning outcomes of the Biology Education Study Program are 99%, having met the course completion criteria. This result shows that technology also plays a vital role in education, especially distance learning. Lecture activities experience a faster transformation in the use of technology.Abstrak Pembelajaran daring menjadi alternatif solusi dalam proses pembelajaran di era pandemic Covid-19. Teknologi berperan penting sebagai media ajar dalam proses pembelajaran daring. Penelitian ini bertujuan untuk mendeskripsikan hasil belajar mahasiswa program studi Pendidikan Biologi sebanyak 323 orang. Penelitian ini adalah penelitian deskriptif dengan data diperoleh mengunakan instrument lembar observasi untuk mengumpulkan data terkait pembelajaran daring dan dokumentasi skor hasil belajar yang dianalisis menggunakan statistic deskriptif. Teknologi yang digunakan dalam pembelajaran online yaitu Zoom Meeting, Google Metting, Whatsapp, Youtube, dan LMS (Learning Management system) berupa SIMARI. Hasil penelitian ini menunjukkan bahwa rata rata hasil belajar mahasiswa Program Studi Pendidikan Biologi 99% telah memenuhi kriteria ketuntasan mata kuliah. Hal ini menunjukkan bahwa teknologi juga berperan penting pada dunia Pendidikan terutama pada pembelajran jarak jauh. Kegiatan perkuliahan mengalami transformasi lebih cepat dalam penggunaan teknologi.